2020
DOI: 10.1093/jscr/rjaa334
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic maxillary tooth as a cause of recurrent maxillary sinusitis: a case report and review of the literature

Abstract: This article presents a rare case report of an ectopic third molar tooth located in the medial wall of maxillary sinus in a young male manifesting as recurrent sinusitis along with upper jaw pain and postnasal discharge diagnosed with an ectopic tooth and bilateral dentigerous cysts. This article aims to discuss this rare presentation of an ectopic tooth as a cause of recurrent maxillary sinusitis and the endonasal endoscopic management of the case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The differential diagnosis of ectopic teeth in the maxillary sinus includes infections such as: tuberculosis, syphilis or fungal infections with calcification, benign lesions such as hemangioma, osteoma, calcified polyp, enchondroma, foreign bodies (rhinoliths) and malignant lesions such as osteosarcoma and chondrosarcoma must be taken into account (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The differential diagnosis of ectopic teeth in the maxillary sinus includes infections such as: tuberculosis, syphilis or fungal infections with calcification, benign lesions such as hemangioma, osteoma, calcified polyp, enchondroma, foreign bodies (rhinoliths) and malignant lesions such as osteosarcoma and chondrosarcoma must be taken into account (19).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery in the case of radiographic findings, in which the patient is asymptomatic, will depend on the risk of: fracture or bone deformation, functional problems, infection and the patient's predisposition. In the case that the option of not intervening surgically is chosen, either due to a high age that puts the life of the patient at risk or the absence of symptoms without evidence of cystic lesion, regular follow-up is required through clinical check-ups every 6-8 months (7,18,19,20). In a systematic review conducted by Veerabhadrappa et al (11) concluded that asymptomatic cases of ectopic mandibular dental inclusions require annual follow-up visits with orthopantomography to monitor migration or the appearance of any lesion.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectopic tooth can occur in different positions, such as maxillary sinus [ 3 ] and nasal cavity. [ 4 ] Ectopic tooth often induces no symptom originally; however, as tooth development or secondary infection or cyst, symptoms may emerge.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the oral epithelium and tooth germ cells plays important roles in tooth development [1] . Abnormal interaction or tooth germ cells migrating to abnormal position caused by developmental disturbance, pathological process or iatrogenic activity during embryonic development may be the pathogenesis of ectopic tooth development [2,3] …”
Section: Introductionmentioning
confidence: 99%